Reactivity enhancement of a diphosphene by reversible N-heterocyclic carbene coordination. Issue 18 (9th April 2018) - Dhara, Debabrata; Kalita, Pankaj; Mondal, Subhadip; Narayanan, Ramakirushnan Suriya; Mote, Kaustubh R.; Huch, Volker; Zimmer, Michael; Yildiz, Cem B.; Scheschkewitz, David; Chandrasekhar, Vadapalli; Jana, Anukul
Abstract : The reversible coordination of an N-heterocyclic carbene (NHC) enhances the reactivity of a diphosphene towards hydrolysis and transfer hydrogenation. The hydrolysis is catalytic in NHC. Abstract : Diphosphene Ter Mes P = PTer Mes (1 ; Ter Mes = 2, 6-Mes2 C6 H3 ; Mes = 2, 4, 6-Me3 C6 H2 ) and NHC Me4 2 (NHC Me4 = 1, 3, 4, 5-tetramethylimidazol-2-ylidene) exist in an equilibrium mixture with the NHC Me4 -coordinated diphosphene3 . While uncoordinated1 is inert to hydrolysis, the NHC adduct3 readily undergoes hydrolysis to afford a phosphino-substituted phosphine oxide with the liberation of NHC Me4 . On this basis, conditions suitable for the catalytic use of NHC Me4 were identified. Similarly, while the hydrogenation of free diphosphene1 with H3 N·BH3 is very slow, 3 reacts instantaneously with H3 N·BH3 at room temperature to afford a dihydrodiphosphane.